Predictors of outcomes in hospitalized patients undergoing pacemaker insertion: Analysis from the national inpatient database (2016‐2017). Issue 9 (31st July 2021) - Kichloo, Asim; Shaka, Hafeez; Aljadah, Michael; Amir, Rawan; Albosta, Michael; Jamal, Shakeel; Khan, Muhammad Zia; Wani, Farah; Mir, Khalid Mohiuddin; Kanjwal, Khalil
Abstract: Background: Pacemaker implantation in the U.S. is rising due to an aging population. The aim of this analysis was to identify risk factors associated with increased mortality and complications in hospitalized patients requiring pacemaker implantation. Methods: We performed a retrospective analysis using the National Inpatient Sample database, identifying hospitalized patients who underwent pacemaker implantation using International Classification of Disease, Tenth Revision, Clinical Modification codes. Independent predictors of inpatient mortality were identified using multivariate logistic regression analysis. Results: There were 242, 980 hospitalizations with pacemaker implantation during 2016 and 2017. The most frequently encountered indications for hospitalizations involving pacemaker insertion included sick sinus syndrome (SSS) (27.60%), complete atrioventricular (AV) block (21.57%), and second‐degree AV block (7.83%). Chronic liver disease was associated with the highest adjusted odds of inpatient mortality (aOR = 5.76, 95% CI: 4.46 to 7.44, p  < .001). Comorbid anemia had the highest statistically significant adjusted odds ratio (aOR) for predictors of post‐procedural cardiac complications (aOR = 3.17, 95% CI: 2.81 to 3.58, p  < .001). Mortality in hospitalized patients needing pacemaker implantation was 1.05%. About 3.36% of hospitalizations developed post procedural circulatory complications (PPCC), 2.45% developed sepsis, and 1.84% developed mechanical complications of cardiac electronic devices. Conclusions: We identified several predictors of inpatient mortality in hospitalized patients undergoing pacemaker implantation, including chronic liver disease, protein‐calorie malnutrition, chronic heart failure, anemia, and history of malignancy. Anemia, chronic liver disease, and congestive heart failure were independent predictors of adverse outcomes in such patients.